Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Kesejahteraan Finansial Mahasiswi di Surabaya dengan Perilaku Keuangan sebagai Variabel Mediasi: Penelitian - Ardha Dyah Puspita; Raden Johnny Hadi Raharjo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of financial literacy and financial attitude on the financial well-being of female university students in Surabaya, with financial behavior as a mediating variable. The research employed a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Respondents were active female students in Surabaya, selected using purposive sampling techniques. The results indicate that financial attitude significantly affects financial behavior, which in turn strongly influences financial well-being. However, financial literacy does not have a statistically significant direct effect on financial behavior, although it remains theoretically relevant. Therefore, financial behavior is confirmed as a crucial mediating variable linking financial literacy and attitude to financial well-being. These findings underscore the importance of cultivating healthy financial behaviors as a strategy to improve the financial well-being of students, especially women.